2019
DOI: 10.1128/jvi.02253-18
|View full text |Cite|
|
Sign up to set email alerts
|

An Interaction with PARP-1 and Inhibition of Parylation Contribute to Attenuation of DNA Damage Signaling by the Adenovirus E4orf4 Protein

Abstract: The adenovirus (Ad) E4orf4 protein was reported to contribute to inhibition of ATM- and ATR-regulated DNA damage signaling during Ad infection and following treatment with DNA-damaging drugs. Inhibition of these pathways improved Ad replication, and when expressed alone, E4orf4 sensitized transformed cells to drug-induced toxicity. However, the mechanisms utilized were not identified. Here, we show that E4orf4 associates with the DNA damage sensor poly(ADP-ribose) polymerase 1 (PARP-1) and that the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…In the same vein, activation of sirtuins through resveratrol treatment inhibits adenovirus DNA replication [89, 90]. Another NAD + -dependent enzyme to have been studied in lytic infection is Poly (ADP-Ribose) Polymerase 1 (PARP1); the AdV E4orf4 protein has been found to increase production of viral progeny through inhibition of PARP1, which is activated by the infection-induced DNA damage response (DDR) [91]. PARP-induced synthesis and attachment of long poly (ADP-ribose) chains to proteins has been shown to regulate cellular transcription through chromatin remodeling and modification of transcription factors [92, 93].…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, activation of sirtuins through resveratrol treatment inhibits adenovirus DNA replication [89, 90]. Another NAD + -dependent enzyme to have been studied in lytic infection is Poly (ADP-Ribose) Polymerase 1 (PARP1); the AdV E4orf4 protein has been found to increase production of viral progeny through inhibition of PARP1, which is activated by the infection-induced DNA damage response (DDR) [91]. PARP-induced synthesis and attachment of long poly (ADP-ribose) chains to proteins has been shown to regulate cellular transcription through chromatin remodeling and modification of transcription factors [92, 93].…”
Section: Discussionmentioning
confidence: 99%
“…Mihaela Robu et al [ 37 ] showed that the damaged DNA-binding protein 2(DDB2), a key lesion recognition protein of the global genomic sub-pathway of NER (GG-NER), associates with PARP-1 in the vicinity of UV-damaged chromatin. Furthermore, Keren et al [ 38 ] described an association of E4orf4 with the DNA damage sensor PARP-1. E4orf4 reduces phosphorylation of the enzyme and inhibits its activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to binding DNA-PK, the Ad E4orf4 protein also associates with PARP-1 [ 103 ]. This association requires the activities of at least two E4orf4 partners: protein phosphatase 2A (PP2A) and PARP itself.…”
Section: Targeting Dna Damage Sensors and Ddr Signaling By Adsmentioning
confidence: 99%
“…PARP-1 is recruited to the vicinity of Ad RCs, but recruitment does not require either E4orf4, which is also present in RCs, or PARP activity. E4orf4 was shown to inhibit parylation that was stimulated both by chemically induced DNA damage and by Ad infection, and this inhibition required the interaction of E4orf4 with its major partner, PP2A [ 103 ]. Indeed, PARP-1 appeared to be hypophosphorylated in the presence of E4orf4, and this state of reduced phosphorylation likely contributed to PARP-1’s diminished activity, as phosphorylation of various residues was shown to enhance parylation by PARP-1 [ 154 , 155 ].…”
Section: Targeting Dna Damage Sensors and Ddr Signaling By Adsmentioning
confidence: 99%
See 1 more Smart Citation